The Dental Neglect and Dental Indifference scales compared - Jamieson LM, Thomson WM. (Blackwell Synergy, 2002)
The objective was to determine whether the Dental Neglect and Dental Indifference scales measure similar constructs and have similar associations in the same population sample.